Nanomedicine strategies for sustained, controlled and targeted treatment of cancer stem cells. (December 2016) - Gao, Jie; Li, Wei; Guo, Yajun; Feng, Si-Shen
Cancer stem cells (CSCs) are original cancer cells that are of characteristics associated with normal stem cells. CSCs are toughest against various treatments and thus responsible for cancer metastasis and recurrence. Therefore, development of specific and effective treatment of CSCs plays a key role in improving survival and life quality of cancer patients, especially those in the metastatic stage. Nanomedicine strategies, which include prodrugs, micelles, liposomes and nanoparticles of biodegradable polymers, could substantially improve the therapeutic index of conventional therapeutics due to its manner of sustained, controlled and targeted delivery of high transportation efficiency across the cell membrane and low elimination by intracellular autophagy, and thus provide a practical solution to solve the problem encountered in CSCs treatment. This review gives briefly the latest information to summarize the concept, strategies, mechanisms and current status as well as future promises of nanomedicine strategies for treatment of CSCs.